MORPHOLOGICAL CHARACTERISTICS OF THE HYPOTHYROIDISM OF RAT PUPS BORN TO HYPOTHYROID RAT MOTHERS - Mahmudova Umida Muhiddin qizi; Mamatvaliyev Bunyod Rahmonali o’g’li; Mirzamuxammedov O.X. (Лучшие интеллектуальные исследования, 2024)
The introduction substantiates the relevance and relevance of the study, characterizes the purpose, objectives, object and subject of the study. Compliance with the priority directions of development of science and technology of the Republic is shown, as well as scientific novelty and practical results, the implementation of the results obtained in practical activities, published works and information about the structure of the dissertation are presented.